Right to legal representation: a study on the legal aid department in relation to criminal cases / Wideeya Juliana Mustapha … [et al.] - Mustapha, Wideeya Juliana; Zulkifli, Shaheera; Yunoos, Mashita; Sulong, Nur Diyana (Faculty of Law, 2010)
The Legal Aid Department is administered by the Legal Affair Division in the Prime Minister's Department and it is funded by the government under the Legal Aid Act 1971.The department provides the service of representing the applicants pro-bono in civil and criminal matters but unfortunately, its representative power in criminal matters is limited, showing that it does not comply with Article 5(3), which is right to legal representation, Article 8(1), which is equality before the law, and also the rules of natural justice. Thus, this project paper aims to analyze the Legal Aid Act 1971 on the limitation of the Legal Aid Department's representative power especially in criminal matters. Besides that, from the project paper, it will also suggest appropriate amendment to the Act on matters relating to representation made by the Department. From the research done, it suggested a few recommendations such as amendments to the Legal Aid Act 1971, having one autonomous body, broader scope of representation, having law school clinics, broader allocation of fund by the government and alternative dispute resolution. In the final analysis, it can be concluded that the limited jurisdiction of the Legal Aid Department especially in criminal matters is insufficent to exercise the right of legal representation under Article 5(3) of the Federal Constitution. Thus, it is hope that the suggestions and recommendations which are stated here can be applied in order to make sure that justice can be uphold.